Sleep Duration and Stroke: A Mendelian Randomization Study - Lu, Hui; Wu, Peng-Fei; Li, Rui-Zhuo; Zhang, Wan; Huang, Guo-xiang (Frontiers in Neurology, 2020)
Study objectives: To clarify the effects of sleep duration on stroke and stroke subtypes, we adopted a Mendelian randomization (MR) approach to evaluate their causal relationship. Methods: A genome-wide association study including 446,118 participants from UK biobank was used to identify instruments for short sleep, long sleep and sleep duration. Summary-level data for all stroke, ischemic stroke, intracerebral hemorrhage, and their subtypes were obtained from meta-analyses conducted by the MEGASTROKE consortium. MR analyses were performed using the inverse-variance-weighted method, weighted median estimator, MR pleiotropy residual sum and outlier (MR-PRESSO) test, and MR-Egger regression. Sensitivity analyses were further performed using leave-one-out analysis, MR-PRESSO global test and Cochran’s Q test to verify the robustness of our findings. Results: By two-sample MR, we didn’t find causal associations between sleep duration and risk of stroke. However, in the subgroup analysis, we found weak evidence for short sleep in increasing risk of cardio-embolic stroke (odds ratio [OR], 1.33; 95% confidence interval [CI], 1.11-1.60; P = 0.02) and long sleep in increasing risk of large artery stroke (OR, 1.41; 95%CI, 1.02-1.95; P = 0.04). But the associations were not significant after Bonferroni correction for multiple comparisons. Conclusions: Our study suggests that sleep duration is not causally associated with risk of stroke and its subtypes.